The Leadership in the Tariqah Qadiriyya wa Naqshbandiyya: Characteristics and Sustaining Doctrines - Widiyanto, Asfa (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
This paper was devoting to exploring the nature of leadership in the Tariqah Qadiriyya wa Naqshbandiyya (TQN) by giving some particular attention to the develops of that Tariqah in Mranggen, Central Java. It will investigate the characteristics of the TQN leaders, the doctrines and traditions that sustaining this leadership. In order to develop the nature of leadership in the TQN, it also will be exploring the concept of leadership in Islamic mystical tradition as general. In the TQN, we come across several rituals which sustain the leadership: the rabita (bond with the master) which focuses on the master; a ritual that falls into the authority of the master as initiation; a notion which indicates the authority of the master as silsila; a notion which lies behind (and triggers) the attraction of the master to the people as baraka (blessing); and a tradition which indicates the veneration of the master as the hawliyya (death anniversary).